Regulating International Distribution Terms Protecting Supplier Rights and Regulating Distribution in the Business Growth Sector (International Journal of Financial, Administrative and Economic Sciences, 2025)
Clarity of rights and obligations: Agreements clearly define the supplier's and distributor's obligations, such as the right to use the distributor's trademark and the minimum sales required from the distributor. Reducing disputes and misunderstandings: Clear terms provide assurance that they reduce the likelihood of disagreements or misunderstandings between the parties and facilitate the resolution of disputes should they arise. Building Sustainable Relationships: These agreements help build long-term relationships based on trust and cooperation between the supplier and distributor. Defining Financial Terms: The agreements clearly define prices, payment terms, and discounts, ensuring a stable financial relationship between the two parties. Protecting Interests: The legal framework protects the interests of the principal and distributor upon expiration or non-renewal of the agreement. Business Expansion: Distribution contracts help organize and expand businesses and help products reach wider global markets. Encourage Investment and Competitiveness: A sound regulatory framework helps attract foreign investment and promote fair competition in the market. Ensure Continuity of Services: Agreements ensure the continued availability of goods and services in the market, benefiting consumers and contributing to economic stability. It is also important to ensure that certain key clauses are included in an international distribution contract, including the terms of product distribution between the supplier and distributor, the territories, commissions, contract duration, and dispute resolution mechanisms. These clauses are essential to ensuring the achievement of commercial objectives and protecting the rights of all parties.
Keywords: Supplier Rghts Protection; Distributor Rights Protection; Business Growth